IbM SEKOLAH LUAR BIASA (SLB) ANAK GANGGUAN AUTISM SPECTRUM DISORDER DI KOTA MAKASSAR - Syam, Nasruddin; Gafur, Abd; Hamzah, wardiah (Jurnal BALIRESO, 2017)
Reports from the World Health Organization (WHO) in 2013 stated that the global prevalence ofASD latest median is 62/10 000 or 160 children one of whom had Autism Spectrum Disorder(ASD). The high prevalence of ASD encourages governments and communities establisheducational institutions such as extraordinary school (SLB), to help ASD children can grow anddevelop like other communities. The problem often faced by partners (SLB Laniang, SLB AutisBunda and SLB Pembina Provinsi Sulsel Kota Makassar) is uncertain about how to takemeasurements and mapping ASD child, then the program agreed with the partner, there are two(2) main aspects, namely: (1) identifies and measures the severity of ASD children interferenceand (2) Mapping addresses and locations disorder ASD child home. The results indicate that thereis an increased activity of knowledge of teachers / lecturers to the identification and measurementof children with ASD to use it Childhood Autism Rating Scale (CARS), which has been speciallydesigned using Exel, so that teachers / lecturers can quickly determining the severity of thedisorder ASD children. This activity also has meningkatkatkan bagamana knowledge on how todo the mapping ASD children, especially in Laniang SLB, SLB Autism Mother and SLB Pembinaprovince of Makassar